Detection, Characterization, and Clinical Application of Mesenchymal Stem Cells in Periodontal Ligament Tissue. (26th August 2018) - Tomokiyo, Atsushi; Yoshida, Shinichiro; Hamano, Sayuri; Hasegawa, Daigaku; Sugii, Hideki; Maeda, Hidefumi
Abstract : Mesenchymal stem cells (MSCs) are a kind of somatic stem cells that exert a potential to differentiate into multiple cell types and undergo robust clonal self-renewal; therefore, they are considered as a highly promising stem cell population for tissue engineering. MSCs are identified in various adult organs including dental tissues. Periodontal ligament (PDL) is a highly specialized connective tissue that surrounds the tooth root. PDL also contains MSC population, and many researchers have isolated them and performed their detailed characterization. Here, we review the current understanding of the features and functions of MSC population in PDL tissues and discuss their possibility for the application of PDL regeneration.